Gentamicin coating of plasma chemical oxidized titanium alloy prevents implant-related osteomyelitis in rats. (September 2016) - Diefenbeck, M.; Schrader, C.; Gras, F.; Mückley, T.; Schmidt, J.; Zankovych, S.; Bossert, J.; Jandt, K.D.; Völpel, A.; Sigusch, B.W.; Schubert, H.; Bischoff, S.; et al.
Abstract: Implant related infection is one of the most feared and devastating complication associated with the use of orthopaedic implant devices. Development of anti-infective surfaces is the main strategy to prevent implant contamination, biofilm formation and implant related osteomyelitis. A second concern in orthopaedics is insufficient osseointegration of uncemented implant devices. Recently, we reported on a macroporous titanium-oxide surface (bioactive TiOB) which increases osseointegration and implant fixation. To combine enhanced osseointegration and antibacterial function, the TiOB surfaces were, in addition, modified with a gentamicin coating. A rat osteomyelitis model with bilateral placement of titanium alloy implants was employed to analyse the prophylactic effect of gentamicin-sodiumdodecylsulfate (SDS) and gentamicin-tannic acid coatings in vivo . 20 rats were randomly assigned to four groups: (A) titanium alloy; PBS inoculum (negative control), (B) titanium alloy, Staphylococcus aureus inoculum (positive control), (C) bioactive TiOB with gentamicin-SDS and (D) bioactive TiOB plus gentamicin-tannic acid coating. Contamination of implants, bacterial load of bone powder and radiographic as well as histological signs of implant-related osteomyelitis were evaluated after four weeks. Gentamicin-SDS coating prevented implant contamination in 10 of 10 tibiae and gentamicin-tannic acid coating in 9 of 10 tibiae (infection prophylaxis rate 100% and 90% of cases, respectively). In Group (D) one implant showed colonisation of bacteria (swab of entry point and roll-out test positive for S. aureus ). The interobserver reliability showed no difference in the histologic and radiographic osteomyelitis scores. In both gentamicin coated groups, a significant reduction of the histological osteomyelitis score (geometric mean values: C = 0.111 ± 0.023; D = 0.056 ± 0.006) compared to the positive control group (B: 0.244 ± 0.015; p < 0.05) was observed. The radiographic osteomyelitis scores confirmed these histological findings.